(untitled) (AL-FIKRAH: Jurnal Kajian Islam, 2025)
The Qur’an is the final holy book revealed by Allah (SWT) to the Prophet Muhammad (PBUH) through the angel Jibril, containing teachings of monotheism, worship, law, and moral values, and serving as a guide for Muslims throughout time. In today’s social reality, a phenomenon has emerged known as Qur’anic street performing, where individuals recite Qur’anic verses in public while asking for donations. This study aims to examine the practice from the perspective of Islamic law, focusing on the role of the Qur’an in Muslim life, the social background behind this phenomenon, and scholarly views on the matter. The research uses a literature review method, referring to sources such as tafsir, Islamic jurisprudence, fatwas, and relevant academic works. Findings indicate that although reciting the Qur’an is a noble act of worship, using it as a means of busking is seen as disrespectful to its sanctity. Many scholars argue that such a practice contradicts Islamic principles, as it blends acts of devotion with material gain. Therefore, public education on the proper etiquette of Qur’anic recitation is needed, along with proactive involvement from religious leaders and policymakers to provide wise solutions to this kind of social issue and to urge the public not to give money to those who recite the Qur’an as street performers.